Model Pendidikan Karakter Qur’ani Dalam Surah Yusuf: Analisis Nilai, Konsep, dan Metode Dengan Pendekatan Tafsir Tematik - Edo Ferdian; Malik Ashari; Syamsul Arifin; Ahsan Hakim (Education Reserach Center, 2025)
This study aims to construct a character education model based on the Qur'anic values contained in Surah Yusuf. In the context of the moral crisis and ethical degradation of the younger generation in the digital era, character education needs to be rooted in spiritual and humanistic values in order to shape individuals with morals and integrity. Surah Yusuf provides a complete picture of character education, encompassing intellectual, emotional, spiritual, and social aspects. This study uses a qualitative approach with the thematic interpretation method (tafsir maudhu'i) and content analysis of the verses of Surah Yusuf related to the values of character education. The primary data source is the Qur'an, while secondary sources include classical and modern commentaries such as Al-Tabari, Al-Qurtubi, and Al-Misbah by Quraish Shihab and Fi Zhilalil Qur'an by Sayyid Qutb, as well as contemporary character education theories from Thomas Lickona, Lawrence Kohlberg, Muslich, and Majid and Andayani as a theoretical basis. The research results show that the main values of character education in Surah Yusuf include honesty, patience, responsibility, hard work, steadfast faith, and self-control. The resulting concept of Qur'anic character education emphasizes the integration of monotheism, morals, and the formation of a resilient personality. The educational methods reflected in Surah Yusuf include role models, advice, habituation, and spiritual reflection. Thus, Surah Yusuf can be used as a paradigm for Qur'anic character education that is relevant and applicable in the modern education system.